Ucapan Bahagia dan Hubungannya dengan Khotbah di Bukit Secara Keseluruhan - Naomi Sapan (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2020)
Abstract. The Beatitude is often misunderstood as a beautiful words yet irrelevant and impossible to practice in daily life. However, in the context of the rest of the Sermon on the Mount and Discourses of the entire book of Matthew, the Beatitude is important because the beatitude is the fundamentally values of the citizens of the Kingdom of God. The happiness as the citizen of God’s Kingdom is very began in their inner life because they are be connected to God, so the happiness is only possible if the people have a fellowship with God who extending and flowing His happiness to them. When the people of the Kingdom of God be connected to the world and living in the daily life their function as salt and light to be realized in practical ethics that relating to all aspects of the social and religious community where they are. The condition of 'happiness' is not related to ownership of something material but happiness or be blessed is identical to their identity as citizens of the Kingdom of God. Happiness that begins when someone responds to the calling of repentance and begins life as a citizen of the Kingdom in fellowship with God. Happiness is also not determined by the promise that following. The following promise is a result of their attitude heart as the blessed one. Regarding to the promise, it must be understood as an eschatological expectations; in eschatology